Nature-based solutions for urban development and tourism. Issue 2 (6th September 2019) - Rice, Louis
Abstract : Purpose: The purpose of this paper is to examine how nature-based solutions (NBS) are being used in city areas to improve environmental conditions and increase tourism. This research examines the drivers behind, and impacts of, the application of NBS in city redevelopment projects for tourism. NBS is a term that refers to the use of flora and fauna ecosystems as an approach to resolve problems faced by society. Design/methodology/approach: An interdisciplinary research methodology has been developed to examine the relationship between city NBS and tourism; the methods include a literature review of contemporary practice, field observations and thematic textual analysis from digital archives. The research methodology uses a combined empirical and desk-based analysis of five case studies cites. Findings: NBS, as part of city redevelopment projects, is now a strategic aim of many cities globally to re-brand, re-vision and re-orientate themselves to be more hospitable, liveable and attractive to tourists and visitors. Practical implications: City redevelopment projects are incorporating NBS to address climate change as well as local environmental issues such as disaster resilience whilst simultaneously delivering social and economic benefits. Social implications: The research reveals that NBS can deliver benefits to human wellbeing, tourism, economic vitality as well as more sustainable models of urban development. Originality/value: The research reveals for the first time how NBS is being used as a driver for increasing tourism globally. The research is highly original as it examines a new topic in tourism studies, the role of NBS in relation to city tourism.